Produtividade total dos fatores na agricultura: Brasil e países selecionados - José Garcia Gasques; Eliana Teles Bastos; Mirian Rumenos Piedade Bacchi; José Eustáquio Ribeiro Vieira Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Technological change is a determining factor to ensure the sustainable growth of the agricultural sector in Brazil and worldwide. Since the 70s, Brazil has been able to expand the food supply, thus contributing to the supply of domestic and foreign markets. Between 1980 and 2021, grain production increased by almost 400 percent. The aim of this paper was to calculate and analyze the total factor productivity in Brazil from 1975 to 2020. Furthermore, through the study organized by the United States Department of Agriculture (USDA), it was possible to compare a group of 187 countries. In this international comparison, Brazil stood out for its potential on productivity growth, notably from the 2000s onwards. From 2000 to 2019, total factor productivity in Brazil grew by around 3.2 percent per year, while the same global indicator reached approximately 1.7 percent.
Keywords: O1; O4; Q10; 330; productivity; agriculture; growth